Utilization of Eggshell Waste to Become Liquid Organic Fertilizer (POC) and Pesticides as a Substitute for Regular Fertilizers through Thematic KKN Activities in Pasang Lela Village, North Labuhan Batu Regency - Josef Hadipramana; Enda Novita Sari; Fetra Venny Riza (Universitas Lancang Kuning, 2023)
One of the problems detected in the residents of Pasang Lela Village that, the majority of farmers in Thematic KKN activities, is that the community wants to use eggshell waste that disturbs the environment, but it is not yet known what appropriate technology can be applied to overcome this problem. The purpose of this KKN program is the transfer of appropriate technology to help the community improve the quality of agriculture and improve the family economy. Eggshells are used as Liquid Organic Fertilizer and pesticides. Eggshells contain 97% calcium carbonate as well as 3% other minerals. POC is made by fermentation for 6-10 days with the addition of Effective Microorganisms 4, brown sugar and water. While in the manufacture of pesticides added fine chili. The results of making POC and pesticides at least reduce the impact of dirty environment and the rotten aroma of eggshell waste. Also, people get healthy, effective and economical fertilizers and pesticides, thus helping to reduce family financial expenditures and preserve the surrounding environment with environmentally friendly fertilizers and pesticides.